Transformasi Jagung Manis menjadi Produk Bernilai Tambah: Pemberdayaan Ibu Posyandu melalui Inovasi Nugget Jagung - Astira Kosmawati; Helen Fitri Novianti; Ratu Fania Aprilyanti; Destia Tresna Prima; Ajeng Pramesti; Jajang Japar Sodik; Entris Sutrisno; Mia Nisrina A; Fenti Fatmawati; Wempi Budiana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Corn (Zea mays L.) is an important commodity in Indonesia, but in Citaman Village, Nagreg District, its utilization is still limited to fresh sales with low added value. To address this issue, a community service program was implemented that focused on empowering village women through training in processing corn into corn nuggets as an innovative product with economic value. The activity was designed with a community-based participatory approach that included coordination with village officials, extension sessions, processing demonstrations, hands-on practice, and evaluation through pre- and post-training questionnaires. The results of the activity showed that more than 85% of participants were very satisfied and more than 80% expressed a high interest in developing corn nuggets as a small-scale business opportunity. These findings indicate a significant increase in participants' knowledge, skills, and entrepreneurial motivation. The corn nugget innovation is not only a means of optimizing the use of local commodities, but is also relevant to the global trend of plant-based foods and supports the achievement of the Sustainable Development Goals (SDGs), specifically Zero Hunger, Decent Work and Economic Growth, and Responsible Consumption and Production. Overall, this program proves that local food-based innovation can be used as a model for replicating community empowerment that contributes to strengthening economic resilience while encouraging sustainable development in rural areas.